Activity-based air pollution exposure assessment: Differences between homemakers and cycling commuters. (November 2019) - Lu, Meng; Schmitz, Oliver; Vaartjes, Ilonca; Karssenberg, Derek
Abstract: Long-term air pollution exposure may lead to an increase in incidences and mortality rates of chronic diseases and adversely affect human health. The effects of long-term air pollution exposure have not been comprehensively studied due to the lack of human mobility data collected over a long period. In this study, we develop and apply a personal mobility model to long-term hourly air pollution concentration predictions to quantify personal long-term air pollution exposure for all individuals. We implement our model assuming mobility patterns for commuters and homemakers, and separate between weekdays and weekend. Our results show that NO2 exposure of commuters are on average slightly higher and vary less spatially as they are exposed to NO2 at multiple locations. Highlights: We developed an activity-based stochastic model to quantify long-term all-individual air pollution exposure. The uncertainty of unknown personal working locations is addressed using a Monte Carlo simulation. Our model continuously assesses air pollution exposure over time and can be extended to inter-annual activities. Compared to the homemaker scenario, the scenario assuming bike commuters shows people are exposed to higher air pollution.. The model assessed exposure varies depending on the space-time activities.